Advancing aquaculture probiotic discovery via an innovative protocol for isolation of indigenous, heat and salt tolerant, quorum quenching probiotic candidates - Rwezawula, Philip; Waiswa Mwanja, Wilson; Vereecke, Nick; Bossier, Peter; Vanrompay, Daisy (Frontiers in Microbiology, 2025)
IntroductionThe intensification of aquaculture to meet the growing demand for aquatic animal protein by a global population approaching 10 billion by 2050 has raised concerns about the increased risk of disease outbreaks in farmed species. These diseases account for over 50% of economic losses in commercial aquaculture, largely due to the reliance on ineffective and harmful therapeutic options like antibiotics, which contribute to multidrug resistance and pose serious global health concerns. However, non-antibiotic alternatives such as probiotics have emerged promising choices to enhance growth performance, immunity, and disease resistance in aquaculture species.MethodsIn this study, we present a novel, non-invasive protocol for isolating indigenous bacteria from sediment. This method utilizes minimal media supplemented with N-hexanoyl homoserine lactone (HHL) to select strains with key probiotic attributes.Results and discussionOur study isolated 24 bacterial isolates, 11 demonstrating quorum quenching (QQ) activity by degrading HHL, indicating potential for antivirulence therapy. Among these, eight were non-hemolytic, suggesting safety in the presence of host wounds. Six non-hemolytic isolates exhibited proteolytic activity, which is essential for aiding protein digestion. Whole genome sequencing revealed their identity as Priestia megaterium PMUG01 and PMUG02, Lysinibacillus fusiformis LFUG, Micrococcus yunnanensis MYUG, and two novel species tentatively named Kocuria crassamentum species nova strain KSNUG, and Heyndrickxia crassamentum species nova strain HSNUG. Despite some virulence-associated genes, none of the strains demonstrated pathogenicity in Artemia nauplii. Apart from an lsaB gene in P. megaterium, which confers resistance to lincosamides, no antibiotic resistance genes were detected. Our findings highlight these strains’ biosafety and probiotic potential for aquaculture, offering promising candidates for sustainable disease management and improved feed utilization in farmed species. These results pave the way for developing indigenous and effective, non-antibiotic-based probiotic solutions to mitigate disease risks in aquaculture.